Work Stress and Organizational Climate as Determinants of Job Satisfaction Among Employees of the Education Sub-Department, Region I, East Jakarta Administrative City - Permatasari, Rita Intan; Sugiarti, Rita (Universitas Negeri Makassar, 2025)
Human resources are a crucial element for the development of the Sub-District Education government agency, Region I, East Jakarta Administrative City, so every year the organization conducts assessments and evaluations to improve employee job satisfaction. This research aims to determine The influence of work stress and organizational climate on the job satisfaction of office PJLP employees at the Education Sub-Department Region I, East Jakarta Administrative City. This type of research uses a quantitative method. The population consists of 96 employees, with a sample of 45 employees based on purposive sampling. Data collection uses a questionnaire with a Likert scale from 1 to 5. The analysis tool uses data analysis including validity tests, reliability tests, normality tests, multiple linear regression, t-tests, F-tests, coefficient of determination, and other tests using SPSS version 25. The research results show that: 1) Work Stress partially has a positive and significant influence on the job satisfaction of office PJLP employees at the Sub-Department Region I, East Jakarta Administrative City, 2) Organizational Climate partially has a positive and significant influence on the job satisfaction of of office PJLP employees at the Sub-Department Region I, East Jakarta Administrative City, 3) Work Stress and Organizational Climate simultaneously have a positive and significant influence on the job of office PJLP employees at the Sub-Department Region I, East Jakarta Administrative City. With a contribution of 44,1%, while 55,9% is influenced by other variables not discussed in this research.